The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/j.1556-6978.2012.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Association for Counselor Education and Supervision Guidelines for Research Mentorship: Development and Implementation

Abstract: The authors describe guidelines endorsed by the Association for Counselor Education and Supervision for research mentorship, including characteristics of mentors and mentees. Suggestions for implementing the guidelines at the individual, program, institution, and professional levels are focused on enhancing mentoring relationships as well as mentees’ research quality and productivity. Research on research mentoring, based on the guidelines, is encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…Since then, ACES leaders have offered preconference workshops (ACES INFORM) for enhancing counseling professionals’ research knowledge and skills. ACES research mentorship guidelines (Borders et al, ; Wester et al, ) and research competencies specific to counseling (Wester & Borders, , in press) have been developed. In addition, Hunt and Trusty () edited a special section of JCD , which provided guidelines for developing and reporting high‐quality research studies in that journal.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, ACES leaders have offered preconference workshops (ACES INFORM) for enhancing counseling professionals’ research knowledge and skills. ACES research mentorship guidelines (Borders et al, ; Wester et al, ) and research competencies specific to counseling (Wester & Borders, , in press) have been developed. In addition, Hunt and Trusty () edited a special section of JCD , which provided guidelines for developing and reporting high‐quality research studies in that journal.…”
Section: Resultsmentioning
confidence: 99%
“…As stated in the Association of Counselor Education and Supervision Guidelines for Mentorship, the main goal of research mentorship is to foster the student's development, taking into account the student's developmental needs (Borders et al, 2012). In discussing the ethical responsibilities that accompany mentorship of undergraduate students, Anderson and Shore (2008) suggested that mentorship requires a respect for the mentee's need for autonomy, along with an awareness of the power differential between the mentor and mentee.…”
Section: Socialization and Identity Developmentmentioning
confidence: 98%
“…Interested readers may wish to consult other sources that cover these important topics (e.g. Borders et al, 2012;Johnson, 2002;Shellito et al, 2001).…”
Section: Future Directions For Mentorship In Counselling Psychology Rmentioning
confidence: 99%
See 1 more Smart Citation
“…In their qualitative study, Protivnak and Foss (2009) found that CES students were more successful when they had mentoring relationships with faculty members with whom they had shared interests, motivations, and professional endeavors. Although mentorship practices have been addressed in the literature pertaining to students who aspire to be counselor educators and researchers (Borders, Wester, Granello, Chang, Hays, Pepperell, & Spurgeon, 2012;Borders, Young, Wester, Murray, Villalba, Lewis, & Mobley, 2011), mentorship for students who aim to be clinicians appears to be less prevalent (Walker, 2006). Protivnak and Foss (2009) also determined that departmental culture influenced CES doctoral students' successful completion of their program and cited examples of collaborative environments where faculty invited students to teach or write, were responsive to students' needs, and generally made students feel included.…”
mentioning
confidence: 99%